2021
DOI: 10.1149/1945-7111/ac035f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced High-Rate Performance of Nanosized Single Crystal ε-VOPO4 with Niobium Substitution for Lithium-Ion Batteries

Abstract: ε-VOPO4 has the potential to be the next high energy density cathode material for lithium-ion batteries due to its high thermal stability and its ability to reversibly intercalate two full Li+, giving a high discharge capacity of 305 mAh g−1. However, vanadyl phosphate materials typically experience poor Li+ kinetics that impedes the high-rate capability at the high voltage plateau. In this work, we applied niobium substitution to improve the high-rate performance of the 4.0 V plateau of ε-VOPO4. Elemental ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Nb has also been substituted in other cathode systems, [46][47][48] with a recent increased interest in its use as a substituent in (Li)VOPO 4 . [49][50][51] Overall, we predict Ti and Nb to have a high probability of successful substitution into LiVOPO 4 . However, due to differences in atomic size and bonding characteristics, substitution will also have an effect on the thermodynamic stability of the host material used.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Nb has also been substituted in other cathode systems, [46][47][48] with a recent increased interest in its use as a substituent in (Li)VOPO 4 . [49][50][51] Overall, we predict Ti and Nb to have a high probability of successful substitution into LiVOPO 4 . However, due to differences in atomic size and bonding characteristics, substitution will also have an effect on the thermodynamic stability of the host material used.…”
Section: Introductionmentioning
confidence: 67%
“…Nb has also been substituted in other cathode systems, 46–48 with a recent increased interest in its use as a substituent in (Li)VOPO 4 . 49–51…”
Section: Introductionmentioning
confidence: 99%
“…These efforts have been extended into (Li)VOPO 4 systems as a strategy to improve the reaction kinetics and electrochemical stability at high voltages (i.e., V 5+ /V 4+ redox). 22,[27][28][29][30][31][32][33] In our earlier study, 3.5% Cr-substituted 3-LiVOPO 4 demonstrated better cycling performance than the unsubstituted material, which was attributed to increased reaction reversibility and Li-ion diffusivity in the high-voltage regime. 27 29 In this study, the substitution of V with Nb is implemented for its larger ionic radius and higher bond dissociation energy with O in relation to V (DHf 298 (Nb-O) = 753 kJ mol −1 vs. DHf 298 (V-O) = 618 kJ mol −1 ).…”
Section: Introductionmentioning
confidence: 88%
“…22,[27][28][29][30][31][32][33] In our earlier study, 3.5% Cr-substituted 3-LiVOPO 4 demonstrated better cycling performance than the unsubstituted material, which was attributed to increased reaction reversibility and Li-ion diffusivity in the high-voltage regime. 27 29 In this study, the substitution of V with Nb is implemented for its larger ionic radius and higher bond dissociation energy with O in relation to V (DHf 298 (Nb-O) = 753 kJ mol −1 vs. DHf 298 (V-O) = 618 kJ mol −1 ). 34 It is hypothesized that Nb substitution at the V-site would enlarge the diffusion channel to facilitate faster Li-ion diffusion in the high-voltage region.…”
Section: Introductionmentioning
confidence: 88%
“…It has been proved that this heterogeneity strongly depends on the particle dimensions and geometries, the nature of the interfaces and the relative positioning of the particles within the electrode architecture. 10,11 For example, Luo et al have shown that, in contrast to its bulk counterpart, which showed an extended phase coexistence, nanosized V 2 O 5 undergoes consecutive transformations with minimal phase coexistence on discharge since it possesses higher porosity and thus faster Li-ion diffusion. 12 Therefore, the lattice-mismatched phase boundaries and the corresponding stress could be circumvented.…”
Section: Introductionmentioning
confidence: 99%